Masalah Perencanaan Studi Lanjut Peserta Didik pada Masa Pandemi Covid-19 - Agus Wibowo; Dini Noviana Sari (Universitas Muhammadiyah Metro, 2021)
The formulation of the problems in this study were (1) the problem of planning for further studies during the covid-19 pandemic experienced by students of SMP Negeri 7 Metro (2) How do students overcome the problem of planning for further studies during the covid-19 pandemic. The objectives of this study were (1) to find out the problem of planning for further studies during the covid-19 pandemic (2) to find out that students overcome the problem of planning for further studiens during the covid-19 pandemic . This type of research is descriptive qualitive. The reseasrch used is through the interview method. The data source is students. Data were analyzed by data validity stages using triangulation techniques. Data analysis using data collection, data reduction, data presentation, drawing coclusions. The conclusions in this study are (1) students experience problems with planning with planning for further studies during the covid-19 pandemic, such as students understanding the type of school, the suitability of talents with the school chosen, the suitability of ideals with the chosen major, students do not know the system zoning (2) How students solve the problemof planning their follow-up study by asking teachers at school, asking parents, asking alumni, and looking for information via the internet.